The Portrayal of Antihero in Mario Puzo’s The Godfather (1969) - Mohamad Sidiq Femy Hadirojaq (Passage, 2019)
This study aims to discover how the antihero is portrayed by Michael Corleone in The Godfather (1969) novel by Mario Puzo. The data were in the forms of words, phrases, sentences, and dialogues between the characters in the novel, which were then categorized into four types of characterization according to Rimmon-Kenan (2003), namely act, appearance, speech, and environment. Furthermore, the data were framed by conflictual points while identifying certain events and narrations that are considered as the portrayal of an antihero using the theory of antihero by Wilson et al. (2013). The data were then analyzed through a descriptive qualitative method to obtain deeper explanation and understanding. The result shows that the novel portrays Michael Corleone as an antihero for having the identical characteristics of an antihero proposed by Wilson et al. (2013), namely empathy, humility, self-awareness, flexibility, and an ability to acknowledge the uncertainty. Therefore, it is found that the characteristics of an antihero are not entirely dominated by negative traits as argued by Pangestu (2017), Jati (2018), and Garcia (2013). An antihero may have some negative traits, but they also have some positive ones. The findings of this study also indicate that the original antihero is the antithesis of a hero because an antihero portrays human nature in general. Keywords: antihero, portrayal, characterization